Optimization of an Input Filter for a Three-Phase Matrix Converter - Boztas, Gullu (My University, 2020)
This study includes an optimization of the input filter for three-phase matrix converters. An input filter effects on the power factor while improving the Total Harmonic Distortion (THD) of the input current. Unity power factor being one of the most important advantages of matrix converters will be eliminated if this is not taken into consideration. For this reason, an optimization was used by taking both parameters into consideration in this study. A Particle Swarm Optimization (PSO) algorithm was used in order to reduce the THD of the input current about 3 % with nearly unit power factor as 0.985. The first of the optimization objective functions is to decrease the THD of the input current, and the second is to increase the power factor. The matrix converter was used for a constant frequency and modulation by using the switching strategy of Venturini Method and feeds an RL load. The optimized input filter was analyzed in detail in MATLAB/SimPowerSystems environment and examined in the results. Additionally, FFT spectra of the input and output waveforms are given in the results. Thus, the most suitable input filter was obtained for this system.
Keywords: Mühendislik; Elektrik ve Elektronik; Bilgisayar Bilimleri; Teori ve Metotlar